What Becomes of Nuclear Risk Assessment in Light of Radiation Hormesis? - Jerry M. Cuttler (Dose-Response, 2007)
A nuclear probabilistic risk or safety assessment (PRA or PSA) is a scientific calculation that uses assumptions and models to determine the likelihood of plant or fuel repository failures and the corresponding releases of radioactivity. Estimated radiation doses to the surrounding population are linked inappropriately to risks of cancer death and congenital malformations. Even though PRAs use very pessimistic assumptions, they demonstrate that nuclear power plants and fuel repositories are very safe compared with the health risks of other generating options or other risks that people readily accept. Because of the frightening negative images and the exaggerated safety and health concerns that are communicated, many people judge nuclear risks to be unacceptable and do not favour nuclear plants. Large-scale tests and experience with nuclear accidents demonstrate that even severe accidents expose the public to only low doses of radiation, and a century of research has demonstrated that such exposures are beneficial to health. A scientific basis for this phenomenon now exists. PRAs are valuable tools for improving plant designs, but if nuclear power is to play a significant role in meeting future energy needs, we must communicate its many real benefits and dispel the negative images formed by unscientific extrapolations of harmful effects at high doses.